River Flood Susceptibility Map - Bernhofen, Mark; Trigg, Mark; Sleigh, Andrew; Sampson, Christopher; Smith, Andrew M. (University of Leeds, 2021)
This dataset contains the River Flood Susceptibility Map (RFSM) for 8 different level 1 drainage basins with global coverage. There are two RFSM datasets for each drainage basin. A RFSM of the upstream accumulating area of the flooded river (in km2) and a RFSM of the Strahler stream order of the flooded river. The datasets are in GeoTIFF raster format at a resolution of 1/1200 decimal degrees (~90 m at the equator). Each of the GeoTIFF files is in the WGS84 projection. Also included is a map of the global drainage basins and the corresponding nomenclature. The methodology to produce the data is described in Bernhofen et. al. 2021 "Global Flood Exposure from Different Sized Rivers".
Keywords: FOS: Earth and related environmental sciences